Trastuzumab emtansine with or without pertuzumab versus trastuzumab with taxane for human epidermal growth factor receptor 2–positive advanced breast cancer: Final results from MARIANNE - Perez, Edith A.; Barrios, Carlos; Eiermann, Wolfgang; Toi, Masakazu; Im, Young‐Hyuck; Conte, Pierfranco; Martin, Miguel; Pienkowski, Tadeusz; Pivot, Xavier B.; Burris, Howard A.; Petersen, Jennifer A.; De Haas, Sanne; et al. (Cancer, 2019)
Background In the phase 3 MARIANNE trial, trastuzumab emtansine (T‐DM1) with or without pertuzumab showed noninferior progression‐free survival and better tolerability than trastuzumab plus a taxane (HT) for the first‐line treatment of human epidermal growth factor receptor 2 (HER2)–positive advanced breast cancer. This article reports the final descriptive overall survival (OS) analysis, updated safety data, and additional patient‐reported outcomes and biomarker analyses. Methods OS was assessed in 1095 patients with HER2‐positive breast cancer and no prior therapy for advanced disease who had been randomized to HT, T‐DM1 plus a placebo (hereafter T‐DM1), or T‐DM1 plus pertuzumab (T‐DM1+pertuzumab). A post hoc exploratory landmark analysis of OS, baseline patient and disease characteristics, and tumor biomarkers in patients with and without an objective tumor response (OR) according to the Response Evaluation Criteria in Solid Tumors within 6.5 months of randomization was conducted. Results The median OS was similar across groups (50.9, 53.7, and 51.8 months for the HT, T‐DM1, and T‐DM1+pertuzumab groups, respectively). Among patients with an OR, the median OS was longer with T‐DM1 (64.4 months) and T‐DM1+pertuzumab (not reached) versus HT (56.3 months). No baseline characteristics or biomarkers were strongly associated with OR. The incidence of grade 3 or higher adverse events was greater with HT (55.8%) than T‐DM1 (47.1%) or T‐DM1+pertuzumab (48.6%). The median time to clinically meaningful deterioration (a 3‐point or greater change) in neurotoxicity symptoms was shorter with HT (2.1 months) and T‐DM1+pertuzumab (4.2 months) than T‐DM1 (6.2 months). Fewer patients reported alopecia and diarrhea and were bothered by treatment side effects in the T‐DM1 arm. Conclusions These results support T‐DM1 as a first‐line treatment for patients with HER2‐positive metastatic breast cancer who are deemed unsuitable for taxane‐based therapy. This report presents mature overall survival and safety results with 54 months of follow‐up as well as comprehensive patient‐reported outcomes and a landmark response analysis of the phase 3 MARIANNE trial. These data will provide clinicians with a broader understanding of this relatively new therapy in the first‐line setting, which should illuminate its use in clinical practice.